2000
DOI: 10.1677/joe.0.1640299
|View full text |Cite
|
Sign up to set email alerts
|

hCGbeta core fragment is a metabolite of hCG: evidence from infusion of recombinant hCG

Abstract: The availability of recombinant human chorionic gonadotrophin (r-hCG) has allowed us to measure its metabolic and renal clearance rates and to study the origin of the core fragment of hCG (hCG cf). Serum and urine samples were collected from six subjects, after an intravenous injection of 2 mg (equivalent to 44 000 IU Urinary hCG) r-hCG, and assayed for hCG and the beta subunit (hCG ). Urine from four of the subjects was also subjected to gel chromatography and assayed for hCG cf and hCG.r-hCG, administered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…hCG cf is quantitatively the major form of immunoreactive hCG molecules in pregnancy urine, the concentration of which is 2 to10 times higher than that of intact hCG on a molar basis (Kato & Braunstein 1988, Wehmann et al 1990, de Medeiros et al 1992, and it has been assumed that hCG cf originates from the renal metabolism of intact hCG or free hCG (Wehmann & Nisula 1980, Lefort et al 1984, 1986. However, in a study involving the intravenous injection of recombinant hCG into healthy, non-pregnant women, the hCG cf measured in urine was only 12·2% of the amount of hCG excreted in urine, and it was suggested that there may be more than one pathway responsible for the production of hCG cf in pregnancy (Norman et al 2000). In fact, placental tissue has been associated with the production of hCG cf (Cole & Birken 1988, Udagawa et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…hCG cf is quantitatively the major form of immunoreactive hCG molecules in pregnancy urine, the concentration of which is 2 to10 times higher than that of intact hCG on a molar basis (Kato & Braunstein 1988, Wehmann et al 1990, de Medeiros et al 1992, and it has been assumed that hCG cf originates from the renal metabolism of intact hCG or free hCG (Wehmann & Nisula 1980, Lefort et al 1984, 1986. However, in a study involving the intravenous injection of recombinant hCG into healthy, non-pregnant women, the hCG cf measured in urine was only 12·2% of the amount of hCG excreted in urine, and it was suggested that there may be more than one pathway responsible for the production of hCG cf in pregnancy (Norman et al 2000). In fact, placental tissue has been associated with the production of hCG cf (Cole & Birken 1988, Udagawa et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence, based on clearance studies, that the hCG cf is produced by kidney degradation of circulating hCG (Wehmann et al 1984). A new study using infusion of recombinant hCG reinforces the origin of hCG cf by kidney processing of circulating hCG, but also points to possible multiple pathways of production of hCG cf in urine, as hCG cf was only 12·2% of the amount of hCG excreted in urine whereas, in pregnancy, hCG cf is present in much greater concentrations as compared with hCG (Norman et al 2000).…”
Section: Discussionmentioning
confidence: 77%
“…A series of papers attest to the stability of this terminal metabolite of hCG which is excreted as a remarkably uniform molecule, composed of the hCGβ peptide chain structure of 6-40 disulfide-bridged to 55-92 (Birken et al, 1988;Birken et al, 1996). A series of metabolic studies including human studies by the groups of Nisula and that of Norman both presented data which indicated the hCGβcf was generated predominately by the kidney from hCG presumably absorbed and degraded within the renal tubule structures (de Medeiros et al, 1992a;de Medeiros et al, 1992b;Norman et al, 2000;Wehmann et al, 1984;Wehmann et al, 1989;Wehmann et al, 1990;Wehmann and Nisula, 1980). While authentic hCGβcf has only been isolated from urine and thus, is thought to be solely or mainly a kidney product derived from proteolytic digestion of hCG absorbed from the blood, hLHβcf has been purified both from pituitary tissue as well as from urine and the structures are the same.…”
Section: Discussionmentioning
confidence: 99%